MCP5, a methyl-accepting chemotaxis protein regulated by both the Hk1-Rrp1 and Rrp2-RpoN-RpoS pathways, is required for the immune evasion of Borrelia burgdorferi. - Sajith Raghunandanan; Kai Zhang; Yan Zhang; Raj Priya; Ching Wooen Sze; Yongliang Lou; Michael J Lynch; Brian R Crane; Mark H Kaplan; Chunhao Li; X Frank Yang (PLoS Pathogens)
Borrelia (or Borreliella) burgdorferi, the causative agent of Lyme disease, is a motile and invasive zoonotic pathogen adept at navigating between its arthropod vector and mammalian host. While motility and chemotaxis are well known to be essential for its enzootic cycle, the role of each methyl-accepting chemotaxis proteins (MCPs) in the infectious cycle of B. burgdorferi remains unclear. In this study, we show that mcp5, a gene encoding one of the most abundant MCPs in B. burgdorferi, is differentially expressed in response to environmental signals and at distinct stages of the pathogen's enzootic cycle. Notably, mcp5 expression is regulated by the Hk1-Rrp1 and Rrp2-RpoN-RpoS pathways, two key regulatory pathways that are critical for the spirochete's colonization of the tick vector and mammalian host, respectively. Infection experiments with an mcp5 mutant revealed that spirochetes lacking MCP5 were unable to establish infections in either C3H/HeN mice or Severe Combined Immunodeficiency (SCID) mice, which are deficient in adaptive immunity, underscoring MCP5's critical role in mammalian infection. However, the mcp5 mutant was able to establish infection and disseminate in NOD SCID Gamma (NSG) mice, which are deficient in both adaptive and most innate immune responses, suggesting that MCP5 plays an important role in evading host innate immunity. Moreover, NK cell depletion in C3H and SCID mice restored the infectivity of the mcp5 mutant, further highlighting MCP5's role in evading NK cell-associated immunity. Co-culture assays with NK cells and macrophages revealed that the mcp5 mutant enhanced interferon-gamma production by NK cells. In the tick vector, the mcp5 mutants survived feeding but failed to transmit to mice. These findings reveal that MCP5, regulated by both the Rrp1 and Rrp2 pathways, is critical for establishing infection in mammalian hosts by evading NK cell-mediated host innate immunity and is important for the transmission of spirochetes from ticks to mammalian hosts. This work provides a foundation for further elucidation of chemotactic signals sensed by MCP5 that facilitate B. burgdorferi in evading host defenses.